Book review: Understanding and Promoting Transformative Learning (2nd edition) - Husain, Aisha (Canadian Medical Education Journal, 2023)
This book is a well-crafted guide to Transformative Learning Theory (TLT). Cranton first distills the components of TLT and its evolution. She then shifts focus to the learner’s perspective and individual’s psychological differences. The subsequent chapters look at educator roles to empower learners and lastly how educators can self-reflect and support learners through their own transformative journey.